Nutritional Management of Neonatal Chylous Ascites following Congenital Diaphragmatic Hernia Repair - GS Sanghamitra; Sarat Chandra Gullapalli; Prakash Amboiram (JCDR Research and Publications Pvt. Ltd., 2017)
Chylous ascites is characterised by accumulation of lymph in the peritoneal cavity and is a recognised complication of congenital diaphragmatic hernia repair. We report a case of neonatal chylous ascites that occurred as a complication of congenital diaphragmatic hernia repair and its successful nutritional management with a cost effective skimmed milk based preparation.